2009
DOI: 10.1017/s0022381609990181
|View full text |Cite
|
Sign up to set email alerts
|

Political Prowess or “Lady Luck”? Evaluating Chief Executives’ Legislative Success Rates

Abstract: How successful should we expect chief executives to be in their relationships with the legislature? Answering this question is key to making judgments about the political prowess and lawmaking abilities of particular rulers. I introduce a standard to compare the actual performances of chief executives around the world based on the notion that variations in chief executives' legislative success rates stem from the unpredictability of legislators' behavior. The results underscore the role of uncertainty in statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 24 publications
2
41
0
4
Order By: Relevance
“…Since most bills from either branch are single‐authored, we take this as qualified support for H1b as well. These results are consistent with Saiegh's (2009) findings on presidential “batting averages”, which suggest that executives generally are more successful in getting their bills passed.…”
Section: Analysis and Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Since most bills from either branch are single‐authored, we take this as qualified support for H1b as well. These results are consistent with Saiegh's (2009) findings on presidential “batting averages”, which suggest that executives generally are more successful in getting their bills passed.…”
Section: Analysis and Resultssupporting
confidence: 88%
“…For instance, Calvo (2004) found that Argentine presidents were more likely to pass their bills when they had a majority support in the congress. Similarly, Saiegh (2009) concludes that region‐wide presidents with majority support were more likely to get their bills passed. Thus, we would expect that presidents whose party controlled a legislative majority should be more likely to get their bills passed.…”
Section: Determinants Of Legislative Successmentioning
confidence: 98%
See 1 more Smart Citation
“…My own data show that the incidence of riots is inversely correlated with electoral turnout. Perhaps most telling is the evidence offered by Saiegh (2009, reproduced with his permission) that shows that the incidence of riots is high when democratic governments are either not at all effective or when the legislature is just a rubber stamp (see Figure 5).…”
Section: Mechanismsmentioning
confidence: 99%
“…After describing the key properties of the tax legislative network in Argentina, we estimate models of legislative success, that is, the rate of approval of initiatives in Congress (Canes‐Wrone and Marchi ; Mayhew ; Saiegh ; Tam Cho and Fowler ). Results provide evidence that initiatives that take as sources a larger number of (important) laws are less likely to be approved.…”
mentioning
confidence: 99%